Chemical Synthesis and Properties of Novel Bi2Se3 Nanostructures and Microplatelets. (28th September 2012) - Muiva, Cosmas M.; Moditswe, Charles; Sathiaraj, T. Stephen
Abstract : Bi2 Se3 nanostructures, microsised fibre bundles, and platelets have been synthesised through a simple chemical spray pyrolysis route on glass substrates. Low substrate temperatures (T sub ) favoured growth of nanostructures while elevated T sub was accompanied by increased grain growth and formation of microsised platelets. The nanostructures were identified as nanorods, nanofibers, nanotubes, nanoflowers, and nanoneedles of various aspect ratios. There was an observed red shift of the optical band gap (E g o p t ) with increased T sub from 2.40 eV at 95°C to 1.25 eV at 360°C. Thermo probe measurements confirmed n-type conductivity with dark resistivities which followed a near exponential decline with elevated T sub . The observed changes in optoelectronic properties existing in the different T sub regimes were explained on the basis of microstructural and textural changes in the pristine clusters.